Analyzed Factors That Leads to the Balanced Scorecard Nursing Care Documentation at Rumah Sakit Jiwa Menur Surabaya - Yuli Anggraini; Purwaningsih Purwaningsih; Eka Misbahatul (Jurnal Ners, 2010)
Introduction: Nursing documentation is an important aspect of nursing practice so that should be assessed comprehensively. The objective of the study was to analyze the causing factor of nursing care documentation at Rumah Sakit Jiwa Menur Surabaya through balanced scorecard.Methods: This research was an analytical descriptive conducted out on January 2010 at Rumah Sakit Jiwa Menur Surabaya that measured nursing care documentation through four perspectives of balanced scorecard by distributing quisioner to 55 nurses and 69 customers (patient families) using inclusion criteria, and holding personal interview to 3 structural offi cial, 2 functional official, and 6 ward supervisors. Data of nurse education, percentage of trained nurse was gained by checklist. Data were analyzed using content analysis to fi nd the causing factor of nursing documentation within balanced scorecard.Result: The result showed that financial, internal business processes, and learning and growth perspectives had causal relationship with nursing care documentation at Rumah Sakit Jiwa Menur Surabaya, but customer perspective didn’t have direct causal relationship with it.Conclusion: It can be concluded that impractical nursing documentation form especially in dimension of time on assessment, implementation, and evaluation, and comprehension on assessment, absence of physical nursing standards, limited knowledge on nursing documentation evoked by absence of inhouse training about nursing documentation, ineffective supervision and audit were factors which affecting nursing documentation at Rumah Sakit Jiwa Menur Surabaya. The researcher recommended that the hospital manager should modificate the nursing documentation form using NIC & NOC of NANDA and computerized system, compose physical nursing standards, carry out advanced nursing education and inhouse training about nursing care documentation, improve supervision program, and nursing documentation audit.